Mainstreaming civic tech and citizen sensing: a research agenda on co-creation methods, data interfaces, and impact pathways - Raetzsch, Christoph; Hamm, Andrea; Shibuya, Yuya (Frontiers in Environmental Science, 2023)
In this Perspectives article, we propose an interdisciplinary research agenda that addresses citizen science approaches embedded in civic tech initiatives and citizen sensing scenarios. The proposed agenda builds on the Multi-Level Perspective framework (Geels 2019) to inform research on how such ‘niche innovations’ like citizen sensing become mainstreamed in broader socio-technical systems and modes of governance. To support research across use case scenarios and make analyses more comparable internationally, we identify three core areas of interdisciplinary future research and practice development: (1) uses of cocreation methods to develop project objectives and align stakeholders; (2) designs of interfaces for gathering, communicating and archiving civic data for different types of users; and (3) modeling impact pathways of individual projects that include civic tech activists and citizen scientists, academic researchers, journalists, and policymakers. For impact pathways, we highlight the importance of collaborations with data-driven approaches in journalism.